2006
DOI: 10.1007/s10557-006-8971-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Phytoestrogen Genistein on Myocardial Protection, Preconditioning and Oxidative Stress

Abstract: Genistein, at this dose, does not reduce infarct size per se nor abolishes the protection induced by preconditioning, in both ovariectomized and non-ovariectomized animals. Preconditioning offers myocardial protection in animals with intact gonads as well as estrogen deprived; bilateral ovariectomy, at least during short-term, is not associated with larger myocardial infarcts compared to control animals. In addition estrogen deprivation, during short term, as well as genistein do not modify oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Estrogen impact on cardioprotective effects and ovariectomized females is more susceptible to cardioprotective maneuvers [101, 367]. For this reason, male rabbits are usually taken for initial studies.…”
Section: Small Animal Hearts In Situmentioning
confidence: 99%
“…Estrogen impact on cardioprotective effects and ovariectomized females is more susceptible to cardioprotective maneuvers [101, 367]. For this reason, male rabbits are usually taken for initial studies.…”
Section: Small Animal Hearts In Situmentioning
confidence: 99%
“…Moreover, the use of lipid-lowering therapy is strongly influenced by reimbursement criteria revision, and the female gender was identified as a patient-related predictor of low adherence [8,9,10]. The advantages of estrogen supplementation are preserved in early menopause, failing to maintain cardiovascular protection, thus further therapeutic options continue to be studied [11,12,13]. Genistein aglycone (hereinafter referred to as genistein) is a soy isoflavone, which has progressively gained clinical consideration for the management of postmenopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Its molecular structure resembles that of 17β–estradiol and binds the same estrogen-receptors in a dose-dependent manner. Regular supplementation in combination with a Mediterranean-style diet, regular exercise, and medical therapy improve CV risk, endothelial function, and vascular reactivity in MetS women, although, to date, very little data are available concerning the effect of genistein on heart function [12,14,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…We also showed that acute administration of vitamin E reduced infarct size and maintained the beneficial effect of ischemic preconditioning without altering plasma malondialdehyde during ischemia and reperfusion [146]. Moreover, the phytoestrogen genistein did not abolish the protection induced by preconditioning in both ovariectomized and non-ovariectomized rabbits and did not inhibit lipid peroxidation [147]. An in vivo study showed that the administration of N-2-mercapropropionyl glycine 45 min before the sustained ischemia had no effect on infarct size, prevented the protection from one cycle of ischemic preconditioning, but did not prevent the protection from four cycles of ischemic preconditioning in situ in anesthetized rabbits [148].…”
Section: Antioxidants In Preconditioning and Postconditioningmentioning
confidence: 73%